Relationship of physical balance and energy value in sheep rations. - Cox, R.F.; Hughes, J.S. (Kansas Agricultural Experiment Station, 2012)
It has been demonstrated that the rate of gains and the efficiency of feed utilization by fattening lambs are associated closely with the physical nature of the ration. The manner in which physical balance affects feed utilization however is not known. The objects of the experiments now in progress are: 1. To study additional factors associated with the physical balance of the ration, and, 2.to make further tests of the efficiency of bicarbonate of soda in reducing losses arising from the feeding of rations which are improperly balance physically.
Keywords: Sheep; Energy; Bicarbonate